Assessing the Efficacy of Gelatin Composite 3D Scaffolds in Cardiovascular Tissue Engineering: An In Vitro Study - Mohammad Mahdi Safikhani; Azadeh Asefnejad; Rouhollah Mehdinavaz Aghdam; Sadegh Rahmati (Nanochemistry Research)
This research aimed to investigate the potential of combining tissue engineering with conventional treatment methods to address cardiovascular diseases (CVD). The study focused on designing and 3D printing polymeric scaffolds using a composition of sodium alginate/hyaluronic acid/gelatin (SA/HA/Gel), incorporating heparin as a cardiovascular drug. Scaffolds were printed at different angles (30°, 45°, 60°, and 90°) to assess their physical properties. Various analyses, including scanning electron microscopy (SEM), examined factors such as swelling, porosity, degradability, contact angle, and surface morphology. Chemical changes were evaluated using Fourier-transform infrared (FTIR) testing. Biocompatibility was assessed through cell adhesion and survival rate analyses using L929 cells. Results showed that higher contact angles increased porosity (42-60%) and improved mechanical properties (47 MPa to 85 MPa). Swelling and contact angle were minimally affected by the printing angle. The release model coefficients and diffusion coefficient varied with the contact angle, suggesting alterations in the drug release mechanism. The controlled release rate of heparin aligned with scaffold degradation, ensuring efficient delivery during tissue repair. Biological evaluation demonstrated satisfactory cell adhesion, biocompatibility, and absence of toxicity in the 3D-printed scaffolds. However, altering the printing angle could modify biological properties due to changes in scaffold characteristics. This study confirms that 3D-printed SA/HA/Gel scaffolds incorporating heparin exhibit desirable physicochemical and biological attributes, making them suitable for drug release systems in cardiovascular tissue applications.